Iron curtain echoes: The enduring impact of communism and crowdfunding - Nguyen, Thien Le-Hoang; Hsieh, Hui-Ching (Journal of Corporate Finance, 2025)
Do enduring effects of communism on human behaviors persist in the entrepreneurial financial market, particularly in the equity crowdfunding (ECF) market? Our study, utilizing the natural experimental setting provided by the German crowdfunding platform – Companisto – reveals the lingering shadow of communism in the investment strategies of individuals from East Germany. We posit that risk and time preferences shaped during prolonged exposure to communism deter investors from East Germany from making sound contributions to ECF campaigns. Further analyses of the moderating effects of investors' confidence and entrepreneurs' trustworthiness provide insights into their roles in the success of ECF campaigns.